Hand Transplantation—Risks and Benefits - Lúcio, Maria João; Horta, Ricardo (Journal of Hand and Microsurgery, 2020)
Composite tissue allotransplantation (CTA) is the culmination of progress in transplantation, allowing the reconstruction of the hand in amputees. Worldwide, more than 100 procedures have been performed. The aim of this work was to understand the hand allotransplantation approach, making known current aspects, risks, and benefits. A PubMed research was realized between October 2018 and March 2019, including terms like “Hand transplantation” AND “Composite tissue allotransplantation,” “Hand transplantation” AND “Functional outcomes,” “Hand transplantation” AND “Immunosuppression,” “Hand prosthetics,” “Hand Transplantation” AND “Ethics.” There were included papers between 1995 and 2018, with English language, amputee human adults, systematic reviews, and clinical studies. Seventy-two papers were fully evaluated. There are technical aspects that influence the procedure like team coordination or surgical technique. It requires a long-life treatment, which has risks such as toxicity or infections. However, it allows the recovery of fine movements, and independence, to perform detailed tasks. The indications must be carefully considered, because some patients benefit from the use of prosthesis. CTA has become an option for amputees so it is important to do more research, to determine the benefits of this procedure. It is not considered a life-saving procedure, so there is an ethical debate because of the risks.
Keywords: hand allotransplantation; composite tissue allotransplantation; immunosuppression; ethics; functional outcomes; rehabilitation